Health related quality of life in children with sickle cell disease: A systematic review and meta-analysis. (November 2022) - Stokoe, Mehak; Zwicker, Hailey M.; Forbes, Caitlin; Abu-Saris, Nur E.L. Huda; Fay-McClymont, Taryn B.; Désiré, Naddley; Guilcher, Gregory M.T.; Singh, Gurpreet; Leaker, Michael; Yeates, Keith Owen; Russell, K. Brooke; Cho, Sara; et al.
Abstract: This review had three aims: 1) describe the measures used to assess health-related quality of life (HRQL) in pediatric patients diagnosed with sickle cell disease (SCD); 2 ) document the biopsychosocial factors related to HRQL in pediatric patients diagnosed with SCD; and 3) complete a meta-analysis comparing HRQL in pediatric patients diagnosed with SCD to healthy controls. Included studies were published in English, quantitatively assessed HRQL as a primary aim, in both SCD and controls, and included participants between 0 and 21 years of age. The final review included 66 articles, with a total of 8642 participants with SCD, 4 months-21 years of age, and 62, 458 controls, 5–27 years of age. HRQL was predominately measured using the Pediatric Quality of Life Inventory Generic Core and Sickle Cell Disease Module. Meta-analyses revealed children with SCD had significantly worse HRQL compared to healthy controls (standardized mean difference = −0.93, 95% CI = −1.25, −0.61, p < 0.00001). Worse HRQL was associated with more severe SCD, female sex, and pain. The findings indicate that children with SCD are at risk for worse HRQL compared to their healthy peers and their HRQL may be impacted by several biopsychosocial factors. Future research is needed to examine how sociocultural factors uniquely impact this population and their overall quality of life. Highlights: Children with SCD have significantly lower HRQL. Lower HRQL is associated with pain and sex. Future research should examine sociocultural factors impacting this population